Quintessential inflation and non-oscillatory reheating model - Campos, A. H.; Reis, H. C.; Rosenfeld, Rogério [UNESP] (Elsevier, 2004)
A numerical study of the non-oscillatory reheating mechanism in a quintessential inflation context shows that high reheating temperature can be achieved compared with the usual reheating mechanism in which particles are produced gravitationally. We find that even for a very small coupling between the inflaton field and a massless scalar field, the non-oscillatory reheating production of particles dominates over the gravitational production mechanism. © 2004 Published by Elsevier B.V.